2016
DOI: 10.3835/plantgenome2015.07.0058
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping‐by‐Sequencing Analysis for Determining Population Structure of Finger Millet Germplasm of Diverse Origins

Abstract: Finger millet [Eleusine coracana (L.) Gaertn.] is grown mainly by subsistence farmers in arid and semiarid regions of the world. To broaden its genetic base and to boost its production, it is of paramount importance to characterize and genotype the diverse gene pool of this important food and nutritional security crop. However, as a result of nonavailability of the genome sequence of finger millet, the progress could not be made in realizing the molecular basis of unique qualities of the crop. In the present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 56 publications
4
45
0
Order By: Relevance
“…Further, the crop is productive in wide range of environments and growing conditions from Karnataka in South India to foothills and middle hills of Himalayas in North India and Nepal, and throughout the middle-elevation areas of Eastern and Southern Africa (Kumar et al, 2016). Finger millet being a promising source of micronutrients and protein (Malleshi and Klopfenstein, 1998), can play a significant role in alleviation of micronutrient and protein malnutrition, which affects more than one half of the world’s population, especially women and preschool children in most countries of South-east Asia and Africa (Underwood, 2000).…”
Section: Plants: the Power House Of Calciummentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the crop is productive in wide range of environments and growing conditions from Karnataka in South India to foothills and middle hills of Himalayas in North India and Nepal, and throughout the middle-elevation areas of Eastern and Southern Africa (Kumar et al, 2016). Finger millet being a promising source of micronutrients and protein (Malleshi and Klopfenstein, 1998), can play a significant role in alleviation of micronutrient and protein malnutrition, which affects more than one half of the world’s population, especially women and preschool children in most countries of South-east Asia and Africa (Underwood, 2000).…”
Section: Plants: the Power House Of Calciummentioning
confidence: 99%
“…Recently, an effort has been also made to study the genetic make of diverse world finger millet collection and population structure analysis of 113 finger millet accessions using genotyping by sequencing (GBS) (Kumar et al, 2016). This resulted in a genome wide set of 23000 Single Nucleotide Polymorphisms (SNPs) segregating across the entire collection and several thousand SNPs segregating within every accession.…”
Section: Molecular Approaches For Calcium Biofortificationmentioning
confidence: 99%
“…Kumar et al (2016b) identified 23,000 SNPs through genotyping by sequencing (GBS) of 113 diverse finger millet genotypes. Similarly, 23285 SNPs were generated using next-generation sequencing of two cultivated finger millet genotypes, and 92 SNP markers were validated further for genetic diversity in cultivated and wild species of finger millet (Gimode et al, 2016).…”
Section: Molecular Markers For Assessing Genetic Diversity Species Rmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) in candidate genes, therefore, remains a possible cause of variation in grain calcium contents among finger millet genotypes. Hence, a step forward toward GBS analysis of finger millet genotypes for identification of high density SNP markers linked to grain calcium content was recently taken up by Kumar et al (2016b), and 23,000 SNPs were identified from 33 GB of sequencing data. In future, these SNPs could be further analyzed to identify useful marker(s) associated with grain calcium and protein content.…”
Section: Comparative Genomics Applications In the Cropmentioning
confidence: 99%
See 1 more Smart Citation